1996
DOI: 10.2307/1243704
|View full text |Cite
|
Sign up to set email alerts
|

Model Selection and Forecasting Ability of Theory‐Constrained Food Demand Systems

Abstract: Out-of-sample forecasting of annual U.S. per capita food consumption, applying data from 1923 to 1992, is used as a basis for model selection among the absolute price Rotterdam model, a first-differenced linear approximate almost ideal demand system (FDLA/ALIDS) model, and a first-differenced double-log demand system. Conditional-on-price consumption forecasts derived from elasticities are determined to be superior to direct statistical model forecasts. Models with consumer theory imposed through parametric re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 12 publications
0
42
0
1
Order By: Relevance
“…A number of studies have compared model and elasticity-based forecasts using demand systems. These include Gustavsen and Rickertsen (2003), Kastens and Brester (1996), and Muhammad (2007). These studies concluded that demand forecasts derived from elasticities are superior to model-based forecasts.…”
Section: Forecasting Procedures and Import Demand Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have compared model and elasticity-based forecasts using demand systems. These include Gustavsen and Rickertsen (2003), Kastens and Brester (1996), and Muhammad (2007). These studies concluded that demand forecasts derived from elasticities are superior to model-based forecasts.…”
Section: Forecasting Procedures and Import Demand Simulationmentioning
confidence: 99%
“…For instance, Pan, Hudson, and Ethridge (2010) find that the elimination of U.S. cotton programs (direct payments, target price, and loan rate) would raise the world price index for cotton by slightly less than 5% per year over a 5-year period. Following Kastens and Brester (1996), import demand projections are derived using an elasticity-based forecasting equation. The unconditional elasticities are used because they encompass the complete effect of a price change making them more suitable for policy projections.…”
Section: Forecasting Procedures and Import Demand Simulationmentioning
confidence: 99%
“…However, health concerns and a number of other factors contributed 3 The industry standard for demand modeling is the Almost Ideal Demand System of Deaton and Muellbauer (1980). It is used in almost all the work referenced and has been found to produce elasticities with desirable forecasting properties (Kastens and Brester, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The two most widely adopted especially in food demand studies are the Rotterdam model introduced by Theil (1965) and Barten (1969) and Deaton and Muelbauer's (1980) almost ideal demand system (AIDS). Both models are derived from consumer theory, and are used to impose or test behavioral restrictions that are deduced from that theory (Kastens & Brester, 1996). However, neither economic theory nor statistical analysis provides clear a priori criteria for choosing between these two models (Lee, Brown, & Seale, 1994).…”
Section: Introductionmentioning
confidence: 99%